Unitarization of the one-loop graviton-graviton scattering amplitudes and study of the graviball - J.A. Oller; Marcela Peláez (Physics Letters B)
From the graviton-graviton scattering amplitudes calculated perturbatively in quantum gravity to the one-loop order, we develop further a formalism that allows one to calculate infrared-finite partial-wave amplitudes fulfilling perturbative unitarity. As a result of this process a parameter dubbed ln⁡a emerges that separate between infrared and typical external momenta. The resulting partial-wave amplitudes are next unitarized by employing the Inverse Amplitude Method and the algebraic-N/D method. Then, the graviball resonance, with a similar pole position, is confirmed in the S-wave partial-wave amplitude for all unitarization methods, also with respect to the unitarization of only the leading-order amplitude. Although the spectrum of the theory is independent of the specific value of ln⁡a, the requirement for a well-behaved unitarized effective field theory of gravity identifies the optimal range of ln⁡a for our next-to-leading-order calculations as 0.5≲ln⁡a≲1.7. Briefly, we discuss the D-wave scattering that is weaker than the S-wave scattering, repulsive and non-resonant for ln⁡a≈1.